The dawn of Islamic Civilization over Nigeria, and the arrival of Christianity in to it - Zakaria, Othman Sulaiman; Abdul Latif, Fizouri Ben; Sajid, Ali Ali Jbaili (Journal of Islamic Sciences, 2018)
: This research aims to reveal the beginning of Islamic Civilization in Nigerian regions and the way it spread in it; and shows the conditions of Islam and Muslims in the pre - and post - European occupation. The study explains the nature of Christianity arrival in to Nigerian regions; and the relationship between that and the modern colonization in the country. Islam was very old religion in Nigerian regions, arrived and spread in the early dawn of Islam in 46 AH, and since then it has affected the lives of the social and cultural populations; However, the hammer of modern colonialism has started to knock Nigerian regions in the fifth and sixteenth century AD, accompanied by the missionaries carrying the banner of Christianization, and were unable to wipe out the Islamic state of Sheikh Uthman bin Faudy which dominated all of northern regions of Nigeria at the time despite their fierce resistance against the colonizers. Since then, the civilizational conflict with a religious nature has begun between the oldest religion in the region (Islam) and the newly arrived religion (Christianity) in Nigerian regions.
Keywords: Islam; Christianity; Nigeria; European colonization